Parental experiences of childcare in an informal urban settlement: qualitative interview findings from the Nairobi Early Childcare in Slums (NECS) project. Issue 4 (27th April 2023) - Hughes, Robert C; Muendo, Ruth; Bhopal, Sunil S; Onyango, Silas; Kimani-Murage, Elizabeth W; Kirkwood, Betty R; Hill, Zelee; Kitsao-Wekulo, Patricia
Abstract : Objectives: To gain an in-depth understanding of parent/carers' perspectives on, and decision-making about, early childhood care in general, and paid childcare specifically, in informal settlements in Nairobi. Design: In-depth telephone interviews, conducted using a topic guide, were analysed through a combination of deductive and inductive thematic analysis and regular reflexivity meetings. We explored parents' childcare needs and experiences over time, and their perspectives on the provision of paid childcare in the slums. Setting: Three informal settlements or slums in Nairobi: Kibera; Kawangware; and Mukuru-Viwandani. Participants: A purposively selected sample of 21 parental and non-parental carers of children aged under 5 years who were currently living in three Nairobi slums, including men and women, and users and non-users of paid childcare. Results: Childcare is complex, with a plurality of approaches being used. Common strategies include family member provided care (often but not exclusively by mothers, at home or at a place of work), paid childcare and informal or ad hoc arrangements with neighbours. Childcare decision-making in these settings is constrained by economics and the broader context of living in the slum. Paid childcare is frequently used, but is widely understood to be lacking in quality, especially for the poorest. Quality of childcare is understood to comprise a combination of structural factors, such as the physical space, play and learning resources and processes such as interactions between the care provider and children or parents. Conclusions: These findings suggest a need, and opportunity, to improve early childhood care in slums. Understanding parental perspectives on both the deficiencies and valued features of childcare is likely to be vital to informing efforts to improve childcare in these settings.